PERAN MEDIA SOSIAL, KEPUASAN, DAN PENILAIAN PRODUK PADA PEMBELIAN AEROSTREET DI SHOPEE - Aprilya, Dandy; Aqmala, Diana; Taufan Hariyadi, Guruh (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2025)
This study analyzes the impcat of social media, customer satisfaction and product review on Aerostreet shoes purchasing decisions on Shopee. Using a quantitive approach, data was collected through questionnaires from 100 Dian Nuswantoro University students who bought Aerostreet shoes. Data analysis used SPSS, including validity, reliability, classical assumption and hypothesis test. Result show that social media, customer satisfaction and product review significantly influence purchasing decision. This study provides insights for marketers to optimize social media effectiveness and product quality to enhance competitiveness in the digital market.